NILAI-NILAI MODAL SOSIAL YANG TERKANDUNG DALAM PERKEMBANGAN PARIWISATA (STUDI KOTA SOLO) - Arifin Fafan K Kusuma; Darwanto . (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
Solo City is a city with the second highest visit in Central Java. Development of tourism in the city of Solo is not separated from the role of community participation in developing tourism in this city. Public participation can not be separated from the tourism economy. Embedded value of social capital is one of the things that make up the community participation in tourism development. Collective action in the form of public participation can be a catalyst driving the tourism sector in order to grow continuously to stimulate economic growth in the city of Solo. The purpose of this study is to explore the role and value of social capital in the development of community-based tourism. This study applies the concept of social capital to create an understanding of how the public perception is capable of forming or building and participate in the development of tourism. This study used a qualitative research methodology and data collection through semi-structured interview method, FGD (Focus Group Discussion) and observations that made in the field.This study shows social capital through participation of Solo community that made up of expectations that leads to cooperative behavior, as seen from the cognitive aspects such as public perception that considers that the development of tourism has a positive impact (what the people feel) in the economic recovery. Expectations of a better quality of life through the development of tourism can encourage people to form a community to facilitate their participation in the development of tourism. This community serves as a place for discussion for the people in expressing their ideas about the development of tourism (what the people do), it is part of the structural aspects of social capital. Aspects of cognitive and structural aspects in social capital are able to bring the community together with government cooperation within the framework of the legal form of the Calendar of events in the development of tourism in the city of Solo.Keywords : community participation, Social Capital, development of tourism